2021
DOI: 10.1042/etls20200287
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing in non-human forensic genetics

Abstract: The past decade has seen a rapid expansion of non-human forensic genetics coinciding with the development of 2nd and 3rd generation DNA sequencing technologies. Nanopore sequencing is one such technology that offers massively parallel sequencing at a fraction of the capital cost of other sequencing platforms. The application of nanopore sequencing to species identification has already been widely demonstrated in biomonitoring studies and has significant potential for non-human forensic casework, particularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…While several studies have compared nanopore sequencing with NGS such as Illumina sequencing, [37][38][39] relatively few works are directed toward the comparison of MinION sequencing and Sanger sequencing. 40 The interest in using nanopore as a potential alternative sequencing tool to Sanger sequencing are primarily for amplicon-based assays, commonly used in forensic genetics or tracking species in the field. 36,40 Since Sanger and nanopore sequencing are based on completely different technologies and generate a different form of output, the comparison is not straightforward and done through the generation of a consensus sequence from nanopore read sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have compared nanopore sequencing with NGS such as Illumina sequencing, [37][38][39] relatively few works are directed toward the comparison of MinION sequencing and Sanger sequencing. 40 The interest in using nanopore as a potential alternative sequencing tool to Sanger sequencing are primarily for amplicon-based assays, commonly used in forensic genetics or tracking species in the field. 36,40 Since Sanger and nanopore sequencing are based on completely different technologies and generate a different form of output, the comparison is not straightforward and done through the generation of a consensus sequence from nanopore read sequences.…”
Section: Discussionmentioning
confidence: 99%
“…40 The interest in using nanopore as a potential alternative sequencing tool to Sanger sequencing are primarily for amplicon-based assays, commonly used in forensic genetics or tracking species in the field. 36,40 Since Sanger and nanopore sequencing are based on completely different technologies and generate a different form of output, the comparison is not straightforward and done through the generation of a consensus sequence from nanopore read sequences. 20 Among the few comparisons being made for targeted amplicon analysis, Vasiljevic et al reported using nanopore sequencing to identify animal species via the species-diagnostic region of mitochondrial cytochrome b (mtDNA cyt b) gene with an amplicon length of approximately 421 bp.…”
Section: Discussionmentioning
confidence: 99%
“…MinION's main disadvantage is a relatively low read accuracy compared with the highly accurate sequencing of Sanger and Illumina methods, the estimated error rate being between 5 and 15% [30][31][32] despite its constant improvement. Therefore, the analysis of ONT sequence reads is a complex task, particularly when variant detection is required.…”
Section: Discussionmentioning
confidence: 99%
“…The other major cost reduction comes from extremely affordable nanopore sequencing, which has been proposed for use in wildlife forensics (Hall et al, 2020;Ogden et al, 2021). Although we used more flowcells to recover the 2346 barcodes than Srivathsan et al (2021), owing to the overall poor quality of our samples, each barcode still costs <USD1 to sequence.…”
Section: Rapid Genotyping With Ont Barcodes For Large Seizuresmentioning
confidence: 99%